EVALUASI KEBIJAKAN PENGATURAN PASAR TRADISIONAL â€œPASAR BULUâ€ DI KOTA SEMARANG - Dwirahayu, Intan Agustina; Marom, Aufarul; Subowo, Ari (Journal of Public Policy and Management Review, 2015)
The goal of traditional market policy is to increase local government economy growth. During year of 2011-2013 the retribution in Bulu Market decreased which has impact to local government income. The purpose of this research is to evaluate and excavate the factors which obstruct traditional market policy in Bulu Market. The research methods which are used are Qualitative research method in descriptive type, with interview, observations, and literature study to gather data. The result of traditional market regulation policy in Bulu Market, using public policy evaluation criteria from William Dunn such as, effectivity, efficiency, sufficiency, alignment, responsiveness, and accuracy indicates that the renovation, area regulation and zoning regarded as not optimal. The initial concept of the Bulu Market is as one of the culinary tourism destination by providing food court on the 3rd floor till now hasn’t realized. Sellers preferred selling in the basement. Market facilities hasn’t completed and. The awareness of sellers in maintaining the cleanliness of the merchandise as well as the environment are still lacking. The policy obstruction, area regulation and zoning in Bulu Market which are run not in their way because more of the sellers who choose to sell in market’s basement than in the fixed zones. Based on this result, the traditional market policy hasn’t been optimal. Researcher advices Market Office to do regular evaluation in every three months to the sellers in Bulu Market regarding the kiosk permit. The purpose of the evaluation is to make the sellers in Bulu Market could choose to keep selling in fixed zones or in basement.